Pengembangan Sistem RFID dan Fingerprint Terintegrasi dengan Sistem Otomasi Layanan di Perpustakaan Universitas Brawijaya - Kurniasih Yuni Pratiwi; Suprihatin Suprihatin; Pitoyo Widhi Atmoko (Central Library of Universitas Sebelas Maret, 2020)
The guest book used at Brawijaya University is digital, where visitor data is stored in a MySQL database. The use of barcode systems is quite effective compared to manual books that are manual, however, the barcode is printed, so that if too often affected by friction, the barcode can be damaged, to overcome the weaknesses that are owned by the barcode, the use of RFID technology can be a new alternative , because RFID (tag) is a technology in the form of an embedded chip. This research methodology discusses the framework carried out in the development of RFID and Fingerprint as an alternative to library guest book registration.In the implementation of NodeMCU and fingerprint sensor to the library guest book database with VB.Net GUI, it can be implemented well. Data filling on RFID cards can be done on data blocks, ie blocks other than trailer blocks and manufacturer blocks. Recording in the library guest book database can be done by comparing the registration time of students, if students register on the same day, then recording is only done once, ie at the beginning of registration. Recording can be done using queries directly embedded in the GUI, or calling functions / procedures stored in the database.